Survival Rate of Cervical Cancer in National Referral Hospital in 2012 - 2014 - Laila Nuranna; Aziz Fahrudin (Acta Medica Indonesiana)
Background: cervical cancer is the third leading cause of female deaths worldwide, and it is the leading cause of female deaths in developing countries. A routine survival evaluation is required to imply the result of the treatment. The aim of this study was to determine the cervical cancer patient survival rate at the Cipto Mangunkusumo hospital as national referral hospital in Indonesia. Methods: our retrospective cohort study utilized the medical records of cervical cancer patients from 2012 to 2014 using total population sampling method. The data analysis was conducted using the Kaplan-Meier curve, log rank test and Cox regression to determine significant associations between variables. Results: there were 1,303 subjects with overall survival rates of cervical cancer up to the fifth year of 76%, 65%, 59%, 43% and 34%, respectively, with a median survival of 1,316 days. There were significant differences of hazard ratio for cancer stage variables (p<0.001), and the Cox regression analysis showed that the factor affecting survival was  cancer stage. Conclusion: the 5-year cervical cancer survival rate at the Cipto Mangunkusumo hospital from 2012 to 2014 was 34%.